Swaddle Bath Mempertahankan Suhu Pada Bayi Prematur - Fauziah Rudhiati; Murtiningsih; Risna Rosaria Indah (AKPER Pasar Rebo, 2019)
The biggest threat to newborns is a change in temperature in the uterus and room temperature that can cause hypothermia. Also, the bathing procedures have a risk of causing hypothermia especially in premature babies. The swaddle bath can prevent heat loss through the mechanism of convection, conduction, evaporation, and radiation. This study aims to determine the effectiveness of swaddle bath in maintaining body temperature stability. 50 premature infants who weigh> 1500 grams and body temperature> 350C-.5037.50C were involved in this study. They are divided into swaddle bath and conventional bath groups. The research method was quasi- experimental pretest-posttest control groups for 1 month at Al Ihsan Public Hospital Regional in West Java. Statistical tests use the Wilcoxon test to test pre and post-test data between each group and Mann Whitney test to test post-test data between two groups. The results of the analysis proved that swaddle bath can maintain body temperature with p value 0.018 <α 0.05. The conclusion of this research is the swaddle bath technique can maintain the stability of the body temperature of premature babies after bathing procedures. It is recommended that swaddle bath can be used as a permanent procedure for bathing premature babies in perinatology care rooms.